The Influence of Using Nearpod on the Students’ Enthusiasm in Classroom Discussion in Class X English at SMAN 2 Pangkep - Aulia, Resky; Sunra, La; Sandra Nani, Feyby (State University of Makassar, 2024)
The use of technology in learning as a means that can improve the quality of learning itself. Nearpod is a platform that allows teachers to create and send interactive learning materials to students via digital devices. This platform provides various features, including slide-based presentations, interactive questionnaires, assignments, and even opportunities for students to participate directly via their devices. This research uses the Classroom Action Research (CAR) method and aims to analyze the effect of using the Nearpod platform on the level of student enthusiasm in class discussion at SMAN 2 Pangkep. Research was carried out through a series of cycles consisting of planning, implementation, observation and reflection stages. At the planning stage, the teacher designs a learning plan that includes the use of the Nearpod platform. The implementation stage involves implementing the learning plan involving class X students. Based on the results of this research, it can be concluded that the use of the attractive Nearpod platform has a positive impact on student participation in English class discussions. Students who engage in learning with the engaging Nearpod platform show a more active level of participation in discussions. They are more courageous in expressing opinions, asking questions, and discussing with classmates. The use of the Nearpod platform has proven itself to be an effective tool for increasing student enthusiasm in class discussions. From the results of the survey conducted, 28 out of 30 students agreed that using Nearpod had had a positive impact on their participation in discussions. Keywords— Nearpod, Classroom Discussion, Students enthusiasm.